2014
DOI: 10.1590/s1517-86922014000100012
|View full text |Cite
|
Sign up to set email alerts
|

A termografia no apoio ao diagnostico de lesao muscular no esporte

Abstract: Correspondência:Eduardo Borba Neves. Rua Marquês do Paraná 418, apto 104, Água Verde.80620-210 -Curitiba, PR, Brasil. RESUMOIntrodução: O rúgbi é um dos esportes que mais ocasionam lesões. A lesão muscular apresenta uma variação térmica localizada, provocando um acréscimo da temperatura local que supostamente pode ser avaliado por meio da mensuração da temperatura. Objetivo: O objetivo deste estudo foi analisar a correlação entre a variação de temperatura da pele em diversos sítios corporais e a variação da CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 25 publications
0
22
1
8
Order By: Relevance
“…During the performance of physical exercise, there is an increased metabolic rate and therefore increased internal heat 1 . This changes the heat balance and activates the mechanism responsible for heat loss mediated by hypothalamic complex feedback system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the performance of physical exercise, there is an increased metabolic rate and therefore increased internal heat 1 . This changes the heat balance and activates the mechanism responsible for heat loss mediated by hypothalamic complex feedback system.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have applied this technique both in trained subjects as untrained by the assessment of muscle thickness, which variation was associated with the occurrence of edema in the post-workout period 9,10 . Several studies 1,[11][12][13] already reported the response of many biomarkers after strength training, but studies using low cost diagnostic imaging tools (as ultrasonography and thermography) are rare. authors 14 have reported a high correlation in the diagnosis of handle repetitive strain injuries (RSI) and work-related musculoskeletal disorders (WMSD) between the assessment by ultrasound and thermography, however, although there are studies evaluating muscle recovery through ultrasound 9,10 or by thermography 1,4 in isolation but there is no known correlation between the results of these assessment tools in the muscular aguda ( post-workout period or the best period to use one or another.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is found mostly in muscles and, on the occasion of fiber rupture due to muscle strain, is released into the blood flow. Therefore, it can be used as an indirect marker of muscular injuries and the intensity of the performed effort (Bandeira, Neves, Barroso, & Nohama, 2013;Bandeira, Neves, Moura, & Nohama, 2014;César, Bara Filho, Lima, Aidar, & Dantas, 2008).…”
Section: Acute Effect Of a Fight Of Mixed Martial Arts (Mma) | 31mentioning
confidence: 99%
“…A maioria das lesões traumáticas do ombro ocorrem durante o tackle [34][35][36][37], que é o fundamento técnico utilizado para derrubar ou impedir o avanço do adversário que está com a posse da bola [38]. Esse gesto esportivo é realizado a partir de uma posição agachada com os braços abduzidos para buscar combater o tronco do oponente, resultando em um impacto anteroposterior nos ombros e braços [37].…”
Section: /7unclassified
“…Lacerações do manguito rotador, lesões de Bankart, SLAP (Superior Labrum Anterior to Posterior Lesion, ou seja, lesão do lábio superior de anterior para posterior) e luxações são as consequências mais comuns dessa manobra [13,[38][39][40]. Além disso, o MND é o mais atingido porque os atletas protegem-se com esse membro enquanto carregam a bola com o MD [34]. Devido a isso, exercícios de fortalecimento dos rotadores do MND, que tenham o objetivo reestabelecer a força muscular desse membro, podem melhorar a estabilização da articulação glenoumeral e, consequentemente, auxiliar na prevenção de lesões traumáticas durante os impactos relacionados ao tackle.…”
Section: /7unclassified